Psychosocial working environment: workplace inspection of the psychosocial working environment in the Nordic countries - Nordic Council of Ministers, Copenhagen; Hansen, Tom; Lidsmoes, Lars Christian; Laursen, Peter; Mathiassen, Leo; Jensen, Anne-Marie; Suhr Raby, Christina; Jurvelius, Hannele; Rintala, Jenny; Rosenberg Søvik, Stian; Schyberg, Pia; Tiborn, Marianne (Copenhagen, 2015)
"This report outlines how the authorities in the five Nordic countries, Denmark, Finland, Iceland, Norway and Sweden, carry out their inspections of the psychosocial working environment at the enterprises. Starting out with a description of the psychosocial risks, the report proceeds with a comparison of the differences between the different national regulations as well as an outline of the similarities. The report offers a comparison of the Nordic working environment strategies and a detailed presentation of the different targets and areas of initiative. It also presents how different methods are used in the selection of enterprises, sectors and job groups for inspection and how the inspectors are trained to carry out the inspections. The report rounds off with a description of the different national inspection methods and how to measure their effects."